Association Between SPATA16 Gene (rs1515442) Polymorphisms and Oligozoospermia in Iraqi Men - Al-Obaidi, Zina FH; Al-Nawab, Nabaa; Fadhil, Yasir B.; Ahmed, Hind M. (Iraqi Journal of Science, 2026)
Genetic factors contribute to impaired spermatogenesis and male infertility. Variants in spermatogenesis genes can increase susceptibility to defects in sperm production. Sperm-associated antigen 16 (SPATA16) plays a key role in Golgi-derived acrosome formation during spermiogenesis. This study investigated whether SPATA16 gene (rs1515442 T/C) polymorphisms are associated with oligozoospermia in an Iraqi cohort. 125 infertile oligozoospermic men were compared to 125 normozoospermic fertile controls. Semen volume, sperm concentration, and motility were significantly reduced in the infertile men. The SPATA16 polymorphism rs1515442 variant (T/C) was genotyped using the tetra-primer amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) method. This technique was employed to compare the infertile oligozoospermic men and fertile controls. Genotype and allele frequencies were compared between groups. The TC heterozygote and CC homozygote genotypes were significantly more prevalent in infertile than fertile men (TC: 15.2% vs 2.4%, p=0.0006; CC: 5.6% vs 0.8%, p=0.0339). The C allele frequency was also significantly higher in infertile men (13.2% vs 2%, p=0.0001). Both infertile oligozoospermic males and fertile controls were evaluated for the Hardy-Weinberg equilibrium (HWE) genotype frequencies for SPATA16 (rs1515442). Both groups showed significant variations from HWE, suggesting possible underlying genetic or population-specific causes of the noted link between the SPATA16 polymorphism and male infertility. This study found an association between SPATA16 gene (rs1515442 T/C) variants and oligozoospermia, suggesting this polymorphism may confer susceptibility to impaired sperm production and male infertility. Additional studies are warranted to confirm the findings.